A highly sensitive and selective fluorescent probe for fluoride anions based on intramolecular charge transfer. (15th October 2015) - Liu, Jingkai; Xu, Zhenghe; Liu, Caiyun; Xu, Lirong; Wang, Zhongpeng; Zhu, Baocun
Abstract: Currently, there is a great need to develop methods for the selective detection of fluoride anions (F – ) owing to their toxicity in the environment and biological function in living systems. In this study, we developed a new fluorescent probe (probe 1) employing a Si–O bond as a highly selective recognition receptor for detecting F – via intramolecular charge transfer. Probe 1 could detect F – quantitatively using the turn‐on fluorescence spectroscopy method with excellent sensitivity in the range of 4–38 μM and a detection limit of 0.26 μM; the detection time was < 17 min. We anticipate that probe 1 would be used widely to monitor F – in the environment. Copyright © 2015 John Wiley & Sons, Ltd.